Birth registration in Nepal: An assessment of progress based on two national surveys - Sharad K. Sharma; Dhruba R. Ghimire; Dadhi Adhikari; Shyam Thapa (Public Library of Science (PLoS), 2023)
Birth registration, an essential component of the civil registration system, is expected to be complete and universal. This study assesses the progress made in recent years and identifies gaps in birth registration in Nepal. Data from the Multiple Indicator Cluster Surveys undertaken in 2014 and 2019 are used for the analysis. The two surveys included a total of 12,007 children under five years of age living with their mothers at the time of the surveys. The survey respondents were 11,821 mothers and 186 caretakers (in the case of those without mothers) of the children. The variations in the proportion of births registered among various subgroups of the children are assessed by performing bivariate analysis and binary logistic regression. Birth registration increased considerably, from 58% (95% CI: 57-59%) in 2014 to 77% (95% CI: 76-78%) in 2019. Several of the disparities between and among the various population subgroups that were evident in the 2014 survey had been considerably reduced or eliminated by 2019. The disparities in registration between boys and girls attenuated over time. Although birth registration increased for all children (ages 0-59 months old), infants still had comparatively lower levels of registration. The relatively disadvantaged provinces showed significant progress between the two survey periods. Considerable and significant progress has been made in birth registration in recent years. However, achieving universal and complete birth registration would require sustaining recent achievements and applying proven strategic interventions to ensure the inclusion of the unregistered births.